Pengaruh Media Pembelajaran Interaktif berbasis Wordwall terhadap Hasil Belajar Siswa Kelas 4 SD Negeri 2 Bendo - Ananda Rizki Purnama Putri; Dya Ayu Agustiana Putri; Ria Fajrin Rizqy Ana (Jurnal Simki Postgraduate, 2025)
Learning outcomes are a reflection of students' cognitive and behavioral changes. The aim of the research is to determine the effect of interactive learning media on the learning outcomes of grade 4 students at SD Negeri 2 Bendo. This research is quantitative with an experimental type. The sampling technique used saturated sampling with 30 respondents. Data collection techniques use learning outcomes tests. The data analysis technique uses the t test (Independent Samples T-Test) in Jamovi 2.3.28. Based on the results of hypothesis testing with the Independent Samples T-Test, the posttest p-value was <0.001, which shows that the p-value is <0.05, which means there is a strong and positive influence. Based on the results of the hypothesis, it was found that there was a significant influence of the interactive learning media Wordwall on the learning outcomes of class IV students at SD Negeri 2 Bendo.